2023
DOI: 10.3389/fmicb.2023.1137611
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of probiotics in augmenting bovine reproductive health: an integrated in vitro, in silico, and in vivo study

Purva Gohil,
Bhavya Nanavati,
Kajal Patel
et al.

Abstract: The aim of this study was to isolate and characterize bovine-vaginal probiotics genotypically and phenotypically using in silico and evaluate their in vivo performance in buffaloes with endometritis. For the in vitro isolation and characterization, vaginal swabs were collected from 34 cows and 17 buffaloes, and 709 primary bacterial isolates with probiotic activity were obtained using MRS agar media. Two isolates Lactiplantibacillus plantarum KUGBRC (LPKUGBRC) and Pediococcus pentosaceus GBRCKU (PPGBRCKU) demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…This was supposed to be due to the initial stimulatory effect of L. buchneri on the local immune system and defence mechanisms [ 112 ]. More recent in vivo studies also reported lowered incidence rates of uterine infections, improved uterine involution, increased fertility, a reduced number of oestrus induction days and increased conception rate in buffalo [ 113 ] or cows [ 114 , 115 ].…”
Section: Treatment Alternatives With Regard To Probioticsmentioning
confidence: 99%
“…This was supposed to be due to the initial stimulatory effect of L. buchneri on the local immune system and defence mechanisms [ 112 ]. More recent in vivo studies also reported lowered incidence rates of uterine infections, improved uterine involution, increased fertility, a reduced number of oestrus induction days and increased conception rate in buffalo [ 113 ] or cows [ 114 , 115 ].…”
Section: Treatment Alternatives With Regard To Probioticsmentioning
confidence: 99%